A study of clinico-demographic profile and ventilatory pulmonary function tests in type 2 diabetes mellitus - Pawar, Dushyant B.; Pawar, Shital D.; Zawar, S. D.; Patil, Dilip R. (International Journal of Research in Medical Sciences, 2017)
Background: Type 2 Diabetes Mellitus (DM) is a non-communicable disease. DM produces damage in small blood vessels characterized by morphologic and biochemical alterations of the capillary basal lamina. These abnormalities have been observed in several organs including the lung. As the prevalence of diabetes is rapidly increasing, it would be important to study pulmonary functions in this sub group. Methods: The present observational study carried out at medicine department. It includes previously diagnosed type 2 DM patients between 31 to 50 years of age, non-smoker, non-pregnant with no major respiratory illness. Ventilatory Pulmonary Function Test (VPFT) which includes FVC, FEV1 and FEV1% were studied in all selected participants. VPFT categorized as per American Thoracic Society (ATS). All collected data analysed using Microsoft Excel 2010. Results: The total of 55 previously diagnosed Type 2 DM cases was recruited. 26 (47.2 %) & 29 (52.7 %) were male & female respectively. 21 (38.2 %) has duration of DM more than 5. 11 (20 %) & 5 (9 %) had neuropathy and retinopathy respectively. 29 (52.7 %) had abnormal pulmonary function test. The Mean FVC (84.11 ± 14.94), Mean FEV1 (84 ± 13.72) & Mean FEV1% was (100.05 ± 7.32) among the study participants. 29 (100.0 %) were restrictive type of abnormality. Conclusion: The reduced lung function is likely being a complication of diabetes mellitus. Lung functions needs to be checked periodically.